The “false bottom” of EU regional policy? The potential detachment of regional policy funding and regional planning strategies - Purkarthofer, Eva (AESOP, 2016)
Looking at the sectoral policies the European Union has a mandate for, regional policy (recently mainly addressed as cohesion policy) can be regarded the most relevant for spatial planning. Though regional policy was never seen as part of what is commonly understood as European spatial planning, its explicit spatial dimension and territorial organization suggest a connection with spatial planning, first and foremost with planning at the urban and regional level. The character of this connection, however, differs between member states and changes with every cohesion policy reform. The 2006 reform seemingly diluted the spatial dimension of regional policy in favor of the objectives of growth, jobs and competitiveness (Dühr, Colomb, & Nadin, 2010). At the same time, however, the reform established sustainable urban development as eligible element in the course of the European Regional Development Fund (ERDF). This was emphasized even more in the subsequent reform in 2013, which stipulated that at least 5% of each country’s ERDF resources shall be allocated to integrated actions for sustainable urban development (European Union, 2013). Although the impact of this regulation will only be visible in a few years’ time, evaluations and academic research from previous programming periods have confirmed that the effects of regional policy go beyond socio-economic impacts, triggered by the sheer redistribution of money within the EU. Instead, regional policy is also affecting spatial planning and planning actors through the ideas on strategic planning, integrated development, partnership, evaluation and the exchange of know-how and best practice that it promotes.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south